2021
DOI: 10.1177/1756284821989178
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in clinical gastroenterology practice: what do patients prefer?

Abstract: Background: The Coronavirus Disease 2019 pandemic has forced major changes on healthcare systems. Maintaining regular patients’ surveillance became a major challenge. Telemedicine has been promoted as an economic and effective way for long distance patient care. Our aim was to study patients’ acceptance and perspectives on telemedicine. Methods: Patients scheduled for clinic appointments were offered telemedicine. Those who agreed were asked to fill in a questionnaire assessing their satisfaction with the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Furthermore, patients were reluctant to arrive at medical centers due to fear of exposure to the virus [81,82]. In order to avoid unnecessary clinic visits, various strategies, such as remote medicine (Telecare, Telemedicine), became highly popular [83]. Capsule endoscopy, from this perspective, may provide complete bowel screening with minimal clinic presence time (only the time needed to swallow the capsule and upload the program), and with no invasive procedure needed [82].…”
Section: Ce and Covid 19mentioning
confidence: 99%
“…Furthermore, patients were reluctant to arrive at medical centers due to fear of exposure to the virus [81,82]. In order to avoid unnecessary clinic visits, various strategies, such as remote medicine (Telecare, Telemedicine), became highly popular [83]. Capsule endoscopy, from this perspective, may provide complete bowel screening with minimal clinic presence time (only the time needed to swallow the capsule and upload the program), and with no invasive procedure needed [82].…”
Section: Ce and Covid 19mentioning
confidence: 99%
“…When possible, in-person visits were replaced by telephone visit or video visit, with different levels of doctors and patients' satisfaction, mostly depending on the type of visit (audio/video), patient's age, diagnosis, socioeconomic status, quality of the available technological devices, and presence of a caregiver [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, international scientific societies suggested implementing telemedicine in order to monitor IBD patients during lockdown [18]. Globally, patients with IBD showed a positive attitude regarding telemedicine consultancies [21,46,47], probably because their age is relatively low and they are aware about using technological tools. To confirm this, a survey conducted in patients with different chronic diseases during the COVID-19 pandemic showed that patients with IBD (especially the younger ones) were the most inclined to accept telemedicine and showed great satisfaction with it [47].…”
Section: Discussionmentioning
confidence: 78%
“…Globally, patients with IBD showed a positive attitude regarding telemedicine consultancies [21,46,47], probably because their age is relatively low and they are aware about using technological tools. To confirm this, a survey conducted in patients with different chronic diseases during the COVID-19 pandemic showed that patients with IBD (especially the younger ones) were the most inclined to accept telemedicine and showed great satisfaction with it [47]. Our results are in line with previous findings, since the rate of satisfaction about remote visits was extremely high (88.3%), particularly because patients reported that they were satisfied about not having to go to the hospital (82.6%).…”
Section: Discussionmentioning
confidence: 99%